The clinical application of 4D (18)F-FDG PET/CT on gross tumor volume delineation for radiotherapy planning in esophageal squamous cell cancer - Wang, Yao-Ching (Oxford University Press, 2012)
A combination of four-dimensional computed tomography with (18)F-fluorodeoxyglucose positron emission tomography (4D CT-FDG PET) was used to delineate gross tumor volume (GTV) in esophageal cancer (EC). Eighteen patients with EC were prospectively enrolled. Using 4D images taken during the respiratory cycle, the average CT image phase was fused with the average FDG PET phase in order to analyze the optimal standardized uptake values (SUV) or threshold. PET-based GTV (GTV(PET)) was determined with eight different threshold methods using the auto-contouring function on the PET workstation. The difference in volume ratio (VR) and conformality index (CI) between GTV(PET) and CT-based GTV (GTV(CT)) was investigated. The image sets via automatic co-registrations of 4D CT-FDG PET were available for 12 patients with 13 GTV(CT) values. The decision coefficient (R(2)) of tumor length difference at the threshold levels of SUV 2.5, SUV 20% and SUV 25% were 0.79, 0.65 and 0.54, respectively. The mean volume of GTV(CT) was 29.41 ± 19.14 ml. The mean VR ranged from 0.30 to 1.48. The optimal VR of 0.98, close to 1, was at SUV 20% or SUV 2.5. The mean CI ranged from 0.28 to 0.58. The best CI was at SUV 20% (0.58) or SUV 2.5 (0.57). The auto-contouring function of the SUV threshold has the potential to assist in contouring the GTV. The SUV threshold setting of SUV 20% or SUV 2.5 achieves the optimal correlation of tumor length, VR, and CI using 4D-PET/CT images.